Enhancing building performance - Mallory-Hill, Shauna; Preiser, Wolfgang F. E.; Watson, Chris (Wiley, 2012)
"Enhancing Building Performance presents the latest BPE work, providing a systematic approach for those who wish to use BPE to deliver improved building performance that is responsive to the needs of stakeholders. With chapters written by experts from around the world the book demonstrates how to apply BPE to enhance building design. Topics covered include: evidence-based and integrative design processes, evaluation methods and tools, and education and knowledge transfer. In addition, case studies provide specific examples of how BPE has been used to study such things as the impact of workplace design on human productivity and innovation"--